Information behavior of international students settling in an unfamiliar geo‐spatial environment. Issue 1 (2014) - Oh, Chi Young; Butler, Brian S.; Lee, Myeong
ABSTRACT: This paper presents the findings from a project about how international students seek and acquire information during their settlement in an unknown geo‐spatial environment. Through semi‐structured interviews, questionnaires, and cognitive mapping with twenty international students, this study examines their information needs, information sources, and settlement experiences in the host country. Findings of the study include their (1) focus on acquiring basic, survival‐related information; (2) active use of internet‐based information sources including online/mobile maps; (3) information behavior of wandering around and information encountering; (4) co‐national social networks playing a key role as information sources. Implications are discussed in ways to further our understanding of international students' information behavior and promote its improvement.